Population of Nubia up to the 16th century BC - Pudło, Aleksandra (Polskie Towarzystwo Antropologiczne, 1999)
The article presents anthropological characteristics (morphological features, paleodemography and paleopathology) of the population inhabiting Nubia from the end of the Upper Paleolithic till the 16th century BC. The material basis for this work consisted of the collections of bones coming from the archeological researches carried out in Nubia.